The land of stories : worlds collide - Colfer, Chris; Dorman, Brandon (New York : Little, Brown and Company, 2017)
Conner, Bree, and their friends from the Land of Stories discover that the fairytale world and the Otherworld are on a collision course that will open a portal connecting the two dimensions in New York, allowing Morina, the witches, the three literary emperors, and the literary army to enter and take over the city, but can Conner stop them and restore order to the fairytale world without the help of his twin sister Alex, who is in Morina's thrall?
Keywords: Magic -- Juvenile fiction; Fantasy fiction